Distribution and phylogeography of Blanford's Fox, Vulpes cana (Carnivora: Canidae), in Africa and the Middle East. Issue 1 (2nd January 2018) - Saleh, Mostafa; Younes, Mahmoud; Basuony, Ali; Abdel-Hamid, Fouad; Nagy, Abdullah; Badry, Ahmad
Abstract : The distribution of Vulpes cana in the extreme eastern Sahara is described on the basis of new photographic and sight records, as well as a recently acquired specimen from south-eastern Egypt. The proven range of this elusive fox now extends about 1000 km south into Africa along the Red Sea coastal mountains. The proven and predicted distribution ranges of this fox are discussed. Its phylogeography and evolutionary relationship to other foxes of the region are gleaned from analysis of mitochondrial cytochrome b DNA sequence and are discussed in light of climatic and paleogeographic history of the area. The results show that the species could have initially moved into Africa during the Pliocene-Pleistocene transition period when several land bridges occurred across the Gulf of Suez. More recent land bridges between the mountains of the Sinai Peninsula and the Eastern Desert of Egypt seem to have developed and disappeared several times during the Pleistocene, possibly allowing genetic exchange between V. cana populations in these two areas. The last of this population exchange and genetic flow between the two areas seems to have ended some 14, 000 years ago when the present Gulf of Suez inundation took place.